2016
DOI: 10.1007/s13594-015-0275-9
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic hydrolysis of camel milk casein and its antioxidant properties

Abstract: The aim of this work was to investigate the enzymatic hydrolysis of whole casein from camel milk with proteolytic enzymes, viz. alcalase, α-chymotrypsin and papain, and to assess the antioxidant activity of hydrolysates. Casein powder was reconstituted (5% TS) and the selected enzymes were added at 1:100 (enzyme/substrate). Hydrolysis was carried out for 6 h at 55°C for alcalase and papain and 37°C for α-chymotrypsin, and samples were drawn at 2-h interval. The hydrolysates were analysed for pH, degree of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
57
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 34 publications
11
57
0
1
Order By: Relevance
“…Camel b-CN showed high antioxidant activity after hydrolysis with chymotrypsin. The results of this study suggest that when camel milk is consumed and digested, the produced peptides start to act as natural antioxidants [65,66,101].…”
Section: Antioxidant Activitymentioning
confidence: 81%
See 2 more Smart Citations
“…Camel b-CN showed high antioxidant activity after hydrolysis with chymotrypsin. The results of this study suggest that when camel milk is consumed and digested, the produced peptides start to act as natural antioxidants [65,66,101].…”
Section: Antioxidant Activitymentioning
confidence: 81%
“…There are reports that camel milk acts as an adjuvant and has medicinal properties, suggesting it contains protective proteins, which may have possible role for enhancing immune defense mechanism [120]. These potential health benefits are obtained through a number of bioactive components in camel milk [63,65]. These components either exist naturally in camel milk or are derived from camel milk protein hydrolysates using proteolytic enzymes and/or fermentation with lactic acid bacteria (LAB) [64,66].…”
Section: Functional Properties and Medicinal Applications Of Camel Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the pro-oxidant effects of bioactive peptides produced after fermentation of camel milk and presence of functional groups such as hydroxyl groups on phenolic compounds [59]. Also, demonstrated that a number of food-derived peptides were capable of interacting and quenching DPPH radicals [10,60]. Escherichia coli (ACCT 8739)…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Addition to, the bioactive peptides are used as health-promoting food supplements or as food grade bio-preservatives in the food industry. The common source of bioactive peptides is egg proteins [8], muscle protein, plant proteins, fish proteins [9], casein [10] and whey proteins [8].…”
Section: Introductionmentioning
confidence: 99%